2022
DOI: 10.3390/foods11030452
|View full text |Cite
|
Sign up to set email alerts
|

Bread Sourdough Lactic Acid Bacteria—Technological, Antimicrobial, Toxin-Degrading, Immune System-, and Faecal Microbiota-Modelling Biological Agents for the Preparation of Food, Nutraceuticals and Feed

Abstract: This review intends to highlight the fact that bread sourdough is a very promising source of technological, antimicrobial, toxin-degrading, immune system-, and faecal microbiota-modelling biological agents for the preparation of food, nutraceuticals, and feed, which has great potential at industrial biotechnology scale. There are many applications of sourdough lactic acid bacteria (LAB), which are the main microorganisms in spontaneous sourdough. In addition to their application as pure technological strains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…A study applying yeast fermentation only for bread making already showed a significant reduction in three fungal toxins spiked in wheat flour ( 227 ). Furthermore, the baking process and the induced heat impact had a strong effect on the mycotoxin contents, as mycotoxins were diminished in a higher extent in the crust than in the crumb of breads ( 228 ).…”
Section: Reduction Of Anti-nutritive Compounds and Contaminantsmentioning
confidence: 99%
“…A study applying yeast fermentation only for bread making already showed a significant reduction in three fungal toxins spiked in wheat flour ( 227 ). Furthermore, the baking process and the induced heat impact had a strong effect on the mycotoxin contents, as mycotoxins were diminished in a higher extent in the crust than in the crumb of breads ( 228 ).…”
Section: Reduction Of Anti-nutritive Compounds and Contaminantsmentioning
confidence: 99%
“…For example, LAB in sour dough can be used in combination with plant- and/or animal-based ingredients. Due to the different mechanisms of action and ideal symbiotic activities, the functional characteristics of the whole combination can be enhanced, and it has good flavor and nutritional value ( 82 ). In addition to the synergistic effect with commensal flora, LAB produce compounds with antimicrobial effects in the defense against pathogens by enhancing the epithelial barrier function of the intestine ( 83 , 84 ).…”
Section: Types Of Probioticsmentioning
confidence: 99%
“…It refers to the inhibition of unwanted or pathogenic microorganisms due to antagonistic microbial interference for nutrient competition and the production of antimicrobial metabolites, such as organic acids, hydrogen peroxide, diacetyl, reuterin, bacteriocins, and other lowmolecular-weight metabolites (Sakaridis et al, 2014). Over the past few decades, LAB has been widely used for the preservation of fermented and cooked meat products, and a variety of strains have been found to be effective against pathogens and spoilage microorganisms (Bartkiene et al, 2020(Bartkiene et al, , 202210.3389/fmicb.2022.1092248 Küley et al, 2020;Zokaityte et al, 2020;Agagündüz et al, 2021Agagündüz et al, , 2022Sharma et al, 2021;Petkova et al, 2022;Rathod et al, 2022;Trakselyte-Rupsiene et al, 2022;Yilmaz et al, 2022a,b). However, research on the biopreservation of fresh poultry meat is quite limited and is even scarcer for fresh fish products.…”
Section: Bio-preservative Propertiesmentioning
confidence: 99%